The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1148/radiol.210937
|View full text |Cite
|
Sign up to set email alerts
|

Improving Radiographic Fracture Recognition Performance and Efficiency Using Artificial Intelligence

Abstract: MUSCULOSKELETAL IMAGINGF racture detection using radiography is one of the most common tasks in patients with high-or low-energy trauma in various clinical settings, including the emergency department, urgent care, and outpatient clinics such as orthopedics, rheumatology, and family medicine. Missed fractures on radiographs are one of the most common causes of diagnostic discrepancies between initial interpretations by nonradiologists or radiology residents and the final read by board-certified radiologists, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 24 publications
6
50
0
Order By: Relevance
“…With the assistance of a CNN model, orthopedic surgeons can achieve an improved sensitivity for fracture detection and a reduced the time to read and interpret CT scans. In a previous fracture classification study of 480 patients, CNN model assistance for radiographic reading by six types of readers (emergency physicians, orthopedists, radiologists, physician assistants, rheumatologists, family physicians) showed a 10.4% improvement in fracture (thoracolumbar spine, rib cage, hip and pelvis, shoulder and clavicle, elbow and arm, hand and wrist, knee and leg, and foot and ankle) detection sensitivity (0.752 vs 0.648; p < 0.001 for superiority) without a reduction in specificity (0.956 vs 0.906, p = 0.001 for noninferiority), and the diagnosis time was shortened by an average of 6.3 s per patient with CNN model assistance ( p = 0.046) 21 . Furthermore, Sato et al developed a CNN classification model from a relatively large dataset of hip fractures on plain radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…With the assistance of a CNN model, orthopedic surgeons can achieve an improved sensitivity for fracture detection and a reduced the time to read and interpret CT scans. In a previous fracture classification study of 480 patients, CNN model assistance for radiographic reading by six types of readers (emergency physicians, orthopedists, radiologists, physician assistants, rheumatologists, family physicians) showed a 10.4% improvement in fracture (thoracolumbar spine, rib cage, hip and pelvis, shoulder and clavicle, elbow and arm, hand and wrist, knee and leg, and foot and ankle) detection sensitivity (0.752 vs 0.648; p < 0.001 for superiority) without a reduction in specificity (0.956 vs 0.906, p = 0.001 for noninferiority), and the diagnosis time was shortened by an average of 6.3 s per patient with CNN model assistance ( p = 0.046) 21 . Furthermore, Sato et al developed a CNN classification model from a relatively large dataset of hip fractures on plain radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…14 In another study, artificial intelligence was also shown to improve radiologists' sensitivity by 10.4% (versus without artificial intelligence) for interpreting musculoskeletal radiographs and to reduce reporting time by 6.3 seconds per examination. 15 Nevertheless, the artificial intelligence should analyse only radiographs that it has been trained to interpret to avoid erroneous anomalies being highlighted on those deemed non-interpretable, which occurred in one case in this study (and has been known to occur with other artificial intelligence tools). 16 Interestingly, in this study, radiologists slightly overestimated the likely performance of the artificial intelligence candidate, assuming that it would perform almost as well as themselves on average and outperform them in at least three of the 10 mock examinations.…”
Section: Policy and Clinical Implicationsmentioning
confidence: 98%
“…All the authors de facto reuse an off-the-shelf architecture designed and pretrained on datasets of natural images, which they fine-tune on private annotated datasets of fractures. This work is based on previous studies of Gleamer [4,6], in which a Mask-RCNN [7] model pre-trained on COCO, is assembled using the De-tectron2 framework [23] and fine-tuned on a private internal dataset of 60,000 radiographs of patients with trauma gathered from 22 institutions and annotated by medical experts.…”
Section: Deep Learning For Fracture Detectionmentioning
confidence: 99%
“…A promising direction to facilitate interpretation and reduce the prevalence of errors is to assist radiologists with a computer-aided diagnosis software. The recent advent of deep learning has made such software capable of improving the performance of radiologists [9] and even outperform experts on their own [4,6].…”
Section: Introductionmentioning
confidence: 99%